AB0652 Pet/mr in large-vessel vasculitis: clinical value for the diagnosis and assessment of disease activity. (12th June 2018) - Laurent, C.; Ricard, L.; Buvat, I.; Fain, O.; Mekinian, A.; Soussan, M.; ,
Abstract : Background: The diagnosis and the activity determination could be challenging in large-vessel vasculitis (LVV). Objectives: The aim of this study was to analyze the value of hybrid PET/MR in LVV. Methods: All consecutive patients with LVV who underwent PET/MR were included. PET/MR patterns were defined as inflammatory in the case of positive PET (grade=3) and abnormal MR (stenosis and/or wall thickening) and fibrous in the case of negative PET (grade 1 or 2) and abnormal MR. Results: Thirteen patients with median age at 67 years (23–87 years) and 10 (77%) females were included, and underwent 18 PET/MR scans. Eleven PET/MR performed at diagnosis (n=4) or relapse (n=7) and 7 in patients in remission. 8/18 (44%) had PET/MR inflammatory pattern and 3/18 (17%) had fibrous pattern. PET/MR were normal in 2/10 (20%) cases of TA versus 5/8 (62%) cases of GCA (p=0.3). The median SUVmax was 3.0 [1.8–8.6] without significative difference between GCA and TA: 3.4 (2.1–8.6) versus 2.6 (1.8–7.1) (p=0.4), respectively. Eleven PET (61%) were performed under treatment, which consisted of steroids with a median dose at 30 mg/day [3–240]. Among 11 patients with active disease, 8 had inflammatory patterns and 3 had normal PET/MR, i.e a sensibility of 73%, and the sensibility increased to 100% in patients with active TA disease. Median SUVmax were 4.7 [2.1–8.6] in patients with active disease versus 2 [1.8–2.6] in patients with remission (p=0.003). Conclusions: PET/MR is a new hybrid modality of imaging which is interesting for the diagnosis and the follow-up of large-vessel vasculitis. References: [1] Soussan M, Nicolas P, Schramm C, Katsahian S, Pop G, Fain O, Mekinian A. Management of large-vessel vasculitis with FDG-PET: a systematic literature review and meta-analysis. Medicine (Baltimore). 2015 Apr;94(14):e 622. [2] Einspieler I, Thürmel K, Pyka T, Eiber M, Wolfram S, Moog P, Reeps C, Essler M. Imaging large vessel vasculitis with fully integrated PET/MR: a pilot study. Eur J Nucl Med Mol Imaging 2015;42:1012–24. [3] Desai MY, Stone JH, Foo TK, Hellmann DB, Lima JA, Bluemke DA. Delayed contrast-enhanced MRI of the aortic wall in Takayasu's arteritis: initial experience. AJR Am J Roentgenol. 2005 May;184(5):1427–31. [4] Rudd JH, Warburton EA, Fryer TD, Jones HA, Clark JC, Antoun N, et al. Imaging atherosclerotic plaque inflammation with [18F]- fluorodeoxyglucose positron emission tomography. Circulation 2002;105:2708–11. [5] Baldursson O, Steinsson K, Björnsson J, Lie JT. Giant cell arteritis in Iceland. An epidemiologic and histopathologic analysis. Arthritis Rheum. 1994 Jul;37(7):1007–12. [6] Gonzalez-Gay MA, Garcia-Porrua C, Llorca J, Gonzalez-Louzao C, Rodriguez-Ledo P. Biopsy-negative giant cell arteritis: clinical spectrum and predictive factors for positive temporal artery biopsy. Semin Arthritis Rheum. 2001 Feb;30(4):249–56. Disclosure of Interest: None declared